Quantification of chitooligosaccharides by FACE method: Determination of combinatory effects of mouse chitinases - Kimura, Masahiro; Umeyama, Takatoshi; Wakita, Satoshi; Okawa, Kazuaki; Sakaguchi, Masayoshi; Matoska, Vaclav; Bauer, Peter O; Oyama, Fumitaka (MethodsX, 2020)
Fluorophore-assisted carbohydrate electrophoresis (FACE) enables detection and quantification of degradation products from artificial and natural chitin substrates such as 4-NP-(GlcNAc)2, (GlcNAc)4 and colloidal chitin. The FACE method has been improved by our group for analysis of chitooligosaccharides in the presence of several buffer systems commonly used in the biochemical evaluation of chitinolytic activities of enzymes at pH 2.0-8.0. FACE is a very sensitive technique detecting picomolar amounts of molecules. We optimized the detection conditions as follows: exposure type, precision; sensitivity, high resolution; exposure time, 5 s. We evaluated the (GlcNAc)2 levels using a standard curve that allows chitooligosaccharides quantification at up to 10 nmol amounts. Using the method presented here, the chitinolytic properties of different chitinases can be compared directly. Serratia chitinase A (ChiA) and chitinase B (ChiB), two well-studied bacterial chitinases, have been shown by HPLC to have a synergistic effect on the chitin degradation rate. Using the FACE method, we determined the combinatory effects of mouse chitotriosidase (Chit1) and acidic mammalian chitinase (AMCase) in natural chitin substrates processing.•FACE is a simple and quantitative method.•Our improved procedure enables the quantification of chitooligosaccharides produced by chitinases at pH 2.0-8.0.•FACE is able to quantify chitooligosaccharides at up to 10 nmol amounts.
Keywords: Chitin degradation; Fluorophore-assisted carbohydrate electrophoresis; Quantitative analysis; Chitinase; Chitooligosaccharides